PELATIHAN PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ETNOMATEMATIKA: Training of Development Learning Media Based on Ethnomathematics - Ni Kadek Rini Purwati; Ni Ketut Erawati; Ni Wayan Sunita; Ni Kadek Putri Dwiani; Ni Putu Restu Trinadi Asih; Maria Fitriana Asni; Orsidian Bili (PUAN INDONESIA, 2023)
Learning with an ethnomathematics approach can improve students' ability to describe meaningful relationships in mathematical concepts and deepen their understanding of mathematics. The development of ethnomathematics-based learning media is interesting to do, especially in areas with strong traditions and culture such as Apuan Bangli Village. However, teachers are not used to utilizing and associating what is in the surrounding environment or existing culture as learning materials and are not accustomed to using and developing innovative media. For this reason, a training program for the development of ethnomathematics-based learning media was implemented to be able to help SD Apuan Bangli teachers in creating meaningful learning for students. This training is divided into three stages, namely the preparation stage, the implementation stage, and the evaluation stage. This training had a positive impact on teachers where it was stated that the material being taught was creative and innovative in terms of making media that fit the student's environment, connecting material with our culture that we are not aware of, and incorporating mathematics into our culture.